Administration of autologous platelet rich plasma and the impact on outcomes of assisted reproduction treatment in infertile women - Kutlu, Pelin; Karabulut, Seda; Korkmaz, Oya (IMR Press, 2021)
Objective: There are diverse findings concerning the use of platelet-rich plasma (PRP) in assisted reproduction treatment (ART) cycles of infertile women with low ovarian reserve, ovarian failure or implantation failure due to endometrial problems. A debate continues regarding the benefit of this technique because of the low number of evidence-based studies. Mechanism: Different PRP preparation methods have been described in the literature, aiming to obtain the highest number of platelets following centrifugation steps. Findings in brief : Research on the use of PRP in female infertility aims to improve the deteriorated hormonal profile, gamete production and implantation of the embryo into the endometrium. Conclusions: This paper reviewed literature evaluating the impact of PRP on the outcomes of subsequent ART cycles in infertile women. PRP is a safe and easy-to-apply procedure and can be used as an 'add-on' therapy in patients with reduced ovarian reserve, ovarian failure or implantation failure prior to the in vitro fertilization (IVF) cycle, although it is still regarded as an empirical treatment method. Further studies should be conducted to enlighten the subject.
Keywords: Infertility; IVF; Platelet-Rich Plasma (PRP); Ovarian Failure